Integrative Analysis of MicroRNA-Mediated Gene Signatures and Pathways Modulating White Blood Cell Count in Childhood Acute Lymphoblastic Leukemia. Issue 12 (11th April 2017) - Ramani, Ritika; Megason, Gail; Schallheim, Jason; Karlson, Cynthia; Vijayakumar, Vani; Vijayakumar, Srinivasan; Hicks, Chindo
MicroRNAs (miRNAs) regulate the expression of protein-coding genes and represent potential biomarkers for childhood acute lymphoblastic leukemia (ALL). However, information linking miRNAs with their messenger RNA (mRNA) target genes modulating white blood cell (WBC) count is lacking. Here, we analyzed miRNAs and gene expression data from pediatric patients with ALL to identify a signature of miRNAs involved in ALL and their mRNA target genes, molecular networks, and biological pathways modulating WBC. We discovered a signature of miRNAs differentially expressed in ALL and a signature of mRNA target genes distinguishing patients with high WBC from patients with low WBC. In addition, we identified molecular networks and biological pathways, among them PI3/AKT, JAK/STAT, IL-17, TGF-β, apoptosis, IL-15, STAT3, IGF-1, FGF, mTOR, VEGF, NF-kB, and P53 signaling pathways, enriched for or targeted by miRNAs. The discovered miRNAs and their target genes and pathways represent potential clinically actionable biomarkers and therapeutic targets.